TRNA‐derived fragment tRF‐1020 ameliorates diabetes‐induced retinal microvascular complications. Issue 20 (20th September 2022) - Ma, Cong; Du, Jianling; Ma, Xiang
Abstract: Transfer RNA (tRNA)‐derived fragments are the non‐coding single‐stranded RNAs involved in several physiological and pathological processes. Herein, we investigated the role of tRF‐1020, a tRNA fragment, in diabetes‐induced retinal microvascular complications. The results showed that the levels of tRF‐1020 expression were down‐regulated in diabetic retinal vessels and retinal endothelial cells following high glucose or H2 O2 stress. Overexpressing tRF‐1020 led to decreased endothelial cell viability, proliferation, migration, and tube formation and alleviated retinal vascular dysfunction as shown by decreased retinal acellular capillaries, vascular leakage, and inflammation. By contrast, tRF‐1020 silencing displayed the opposite effects. tRF‐1020 regulated endothelial angiogenic functions and retinal vascular dysfunction by targeting Wnt signalling. Moreover, the levels of tRF‐1020 expression were reduced in aqueous humour and vitreous samples of the patients with diabetic retinopathy. Collectively, tRF‐1020 is a potential target for the diagnosis and treatment of diabetic retinopathy.